Thioredoxin 1 and glutaredoxin 2 contribute to maintain the phenotype and integrity of neurons following perinatal asphyxia - Romero, Juan Ignacio (2015)
Background Thioredoxin (Trx) family proteins are crucial mediators of cell functions via regulation of the thiol redox state of various key proteins and the levels of the intracellular second messenger hydrogen peroxide. Their expression, localization and functions are altered in various pathologies. Here, we have analyzed the impact of Trx family proteins in neuronal development and recovery, following hypoxia/ischemia and reperfusion. Methods We have analyzed the regulation and potential functions of Trx family proteins during hypoxia/ischemia and reoxygenation of the developing brain in both an animal and a cellular model of perinatal asphyxia. We have analyzed the distribution of 14 Trx family and related proteins in the cerebellum, striatum, and hippocampus, three areas of the rat brain that are especially susceptible to hypoxia. Using SH-SY5Y cells subjected to hypoxia and reoxygenation, we have analyzed the functions of some redoxins suggested by the animal experiment. Results and conclusions We have described/discovered a complex, cell-type and tissue-specific expression pattern following the hypoxia/ischemia and reoxygenation. Particularly, Grx2 and Trx1 showed distinct changes during tissue recovery following hypoxia/ischemia and reoxygenation. Silencing of these proteins in SH-SY5Y cells subjected to hypoxia-reoxygenation confirmed that these proteins are required to maintain the normal neuronal phenotype. General significance These findings demonstrate the significance of redox signaling in cellular pathways. Grx2 and Trx1 contribute significantly to neuronal integrity and could be clinically relevant in neuronal damage following perinatal asphyxia and other neuronal disorders.